PENGARUH PROFESIONALISME, PENGALAMAN KERJA DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT (Studi Pada Auditor Kantor Akuntan Publik Di Surabaya) Tahun 2019 - Sryiyanti, Retno; jianto, Jianto (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThis study is a study that aims to find out: Effect of Auditor Professionalism on Audit Quality, Effect of Auditor Work Experience on Audit Quality, Effect of Auditor Independence on Audit Quality, and Effect of Professionalism, Work Experience and Auditor Independence on Audit Quality. The population of this research is all auditors who work at the Public Accounting Firm (KAP) in Surabaya. The sample used in this study were 50 respondents. The method of collecting data using the questionnaire method. The validity test uses the Pearson Product Moment correlation test, while the reliability test uses Cronbach alpha. Classic assumption tests include normality test, multicollinearity test, heteroscedasticity test and Autocorrelation test. Hypothesis testing in this study uses simple regression analysis, and multiple regression analysis. The results of this study indicate that: (1) Auditor Professionalism has a significant effect on Audit Quality as indicated by Value Professionalism (X1) on audit quality (Y) of 0.016 <ttable 0.05. (2) Auditor Work Experience influences Audit Quality (Y) as indicated by the value of Auditor Work Experience (X2) on Audit Quality (Y) of 0,000 <ttable 0.05. (3) Auditor Independence influences Audit Quality (Y) as indicated by Auditor Independence tcount (X3) to Audit Quality (Y) of 0.012 <from table 0.05. (4) There is a positive and significant influence of Independence, Work Experience and Independence simultaneously influencing Audit Quality as indicated by R2 value of 0.654 or 65.4%, Value of Fcount = 28.947 with a significance level of 0.000 which is smaller than 0.05 and the regression line equation Y = 0.997 + 0.251X1 + 0.385X2 + 0.174 X3 + 0.321. Keywords: Professionalism, Work Experience, Independence and Audit Quality.